Splenomegaly in patients with primary or secondary myelofibrosis who are candidates for allogeneic hematopoietic cell transplantation: a Position Paper on behalf of the Chronic Malignancies Working Party of the EBMT. Issue 1 (January 2023) - Polverelli, Nicola; Hernández-Boluda, Juan Carlos; Czerw, Tomasz; Barbui, Tiziano; D'Adda, Mariella; Deeg, Hans Joachim; Ditschkowski, Markus; Harrison, Claire; Kröger, Nicolaus Martin; Mesa, Ruben; Passamonti, Francesco; Palandri, Francesca; et al.
Summary: Splenomegaly is a hallmark of myelofibrosis, a debilitating haematological malignancy for which the only curative option is allogeneic haematopoietic cell transplantation (HCT). Considerable splenic enlargement might be associated with a higher risk of delayed engraftment and graft failure, increased non-relapse mortality, and worse overall survival after HCT as compared with patients without significantly enlarged splenomegaly. Currently, there are no standardised guidelines to assist transplantation physicians in deciding optimal management of splenomegaly before HCT. Therefore, the aim of this Position Paper is to offer a shared position statement on this issue. An international group of haematologists, transplantation physicians, gastroenterologists, surgeons, radiotherapists, and radiologists with experience in the treatment of myelofibrosis contributed to this Position Paper. The key issues addressed by this group included the assessment, prevalence, and clinical significance of splenomegaly, and the need for a therapeutic intervention before HCT for the control of splenomegaly. Specific scenarios, including splanchnic vein thrombosis and COVID-19, are also discussed. All patients with myelofibrosis must have their spleen size assessed before allogeneic HCT. Myelofibrosis patients with splenomegaly measuring 5 cm and larger, particularly when exceeding 15 cm below the left costal margin, or with splenomegaly-related symptoms, could benefit from treatment with the aim of reducing the spleen size before HCT. In the absence of, or loss of, response, patients with increasing spleen size should be evaluated for second-line options, depending on availability, patient fitness, and centre experience. Splanchnic vein thrombosis is not an absolute contraindication for HCT, but a multidisciplinary approach is warranted. Finally, prevention and treatment of COVID-19 should adhere to standard recommendations for immunocompromised patients.